Metode Pembelajaran Kooperatif Tipe Poster Session Dalam Penguasaan Kosakata Bahasa Jerman - Johar Johar; Wahyu Kurniati Asri; Hasmawati Hasmawati (Phonologie : Journal of Language and Literature, 2021)
Abstract. The purpose of this study was to obtain data and information about the effectiveness of the Poster Session type cooperative learning method in learning German vocabulary for class XI students of SMAN 1 Campalagian, Polewali Mandar Regency (virtual). This type of research is an experimental research that uses a vocabulary mastery test in the application of the Poster Session Type Cooperative Learning Method. Data were analyzed by t-test. The population of this study were students of class XI SMAN 1 Campalagian which consisted of 5 classes. The sample used is a random sample (Random Sampling). The number of samples is 2 classes, namely class XI IPS 5 as an experimental class consisting of 30 students and class XI IPS 2 as a control class consisting of 30 students. The results of data analysis showed th=7.07 > tt=2.002 at a significance level of 0.05. The results showed that the Poster Session method was effective in mastering the German vocabulary of class XI students of SMAN 1 Campalagian, Polewali Mandar Regency (virtual).